2005
DOI: 10.1110/ps.051525505
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from 13C solid‐state NMR spectroscopy for a lamella structure in an alanine–glycine copolypeptide: A model for the crystalline domain of Bombyx mori silk fiber

Abstract: 13 C high-resolution solid-state NMR coupled with selective 13 C isotope-labeling of different Ala one methyl carbons was used to clarify the structure of (AG) 15 peptide in the silk II structure as a model for the crystalline domain of Bombyx mori silk fiber. At the inner part of the peptide, the fraction of the peak at 16.6 ppm of the Ala Cb resonance assigned to b-turn structure increased at 11th and 19th positions. These data indicate the appearance of the most probable lamellar structure having a turn str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
64
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 22 publications
6
64
0
Order By: Relevance
“…This is clearly due to presence of Ser residue. The (AG) 15 with silk I form changed to silk II form after formic acid treatment 4 and therefore formic acid treatment was also applied to (AGSGAG) 5 . The fraction of 16.7 ppm peak was 37% and 44% for [3-13 C]A 11 and [3-13 C]A 19 labeled positions, respectively, after 9MLiBr/ dialysis treatment, and 31% and 36% for the same labeled positions after formic acid treatment.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This is clearly due to presence of Ser residue. The (AG) 15 with silk I form changed to silk II form after formic acid treatment 4 and therefore formic acid treatment was also applied to (AGSGAG) 5 . The fraction of 16.7 ppm peak was 37% and 44% for [3-13 C]A 11 and [3-13 C]A 19 labeled positions, respectively, after 9MLiBr/ dialysis treatment, and 31% and 36% for the same labeled positions after formic acid treatment.…”
Section: Resultsmentioning
confidence: 99%
“…However, multiple existence of AGSGAG sequence appears to modulate the pattern of the hydrogen bonding interactions involving O H group of the Ser side-chains and the backbone C=O oxygen. Our 2 H NMR measurements of uniaxially aligned [3,3-2 H 2 ] Ser-labeled B. mori silk fiber with silk II form, indicated that the dominant conformer of the Ser side-chain is gauche þ and this orientation could be a good candidate for facilitating intermolecular hydrogen bonds with the carbonyl groups on adjacent peptide chains, strongly favoring the -sheet structure as shown in Figure 2. 9 Figure 3 shows Ala C regions in 13 C CP/MAS NMR spectra of (a) IV: (AGSGAG) 4 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations